2006
DOI: 10.1021/ic061041k
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, Structures, Physical Properties, and Theoretical Studies of CeMxOS (M = Cu, Ag; x ≈ 0.8) and CeAgOS

Abstract: Black single crystals of the two nonstoichiometric cerium coinage-metal oxysulfide compounds CeCu(x)OS and CeAg(x)OS (x approximately 0.8) have been prepared by the reactions of Ce2S3 and CuO or Ag2O at 1223 or 1173 K, respectively. A black powder sample of CeAgOS has been prepared by the stoichiometric reaction of Ce2S3, CeO2, Ag2S, and Ag at 1073 K. These isostructural materials crystallize in the ZrSiCuAs structure type with two formula units in the tetragonal space group P4/nmm. Refined crystal structure r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 30 publications
7
61
0
Order By: Relevance
“…At room temperature this sulfide oxide is tetragonal, space group I4/mmm and shows a 75% random copper occupancy within the tetrahedral layer, similar to several CeCu 1Àx SO samples [94,95]. Upon cooling the sample below 240 K, long-range ordering of filled (75%) and vacant (25%) copper sites occurs (Fig.…”
Section: Group-subgroup Schemes -Superstructuresmentioning
confidence: 52%
“…At room temperature this sulfide oxide is tetragonal, space group I4/mmm and shows a 75% random copper occupancy within the tetrahedral layer, similar to several CeCu 1Àx SO samples [94,95]. Upon cooling the sample below 240 K, long-range ordering of filled (75%) and vacant (25%) copper sites occurs (Fig.…”
Section: Group-subgroup Schemes -Superstructuresmentioning
confidence: 52%
“…A more general comparison of the a cell parameters of the AFTCh compounds (A = Eu, Sr, Ba) with the corresponding minimal values (termination points) for the LnOTCh series (CuS: 3.874Å, CuSe: 3.865Å [8]; CuTe: 4.040Å [22]; AgS: 3.926Å [21]; AgSe: 4.028Å, AgTe: 4.233Å [14]) clearly indicates that deformations of the [T 2 Ch 2 ] 2− layers in the AFTCh are much smaller, so existence and relatively easy preparation of the fluoride chalcogenides is not surprising. The only exception yet not clearly understood is SrFAgS where the reason probably lies in low reactivity of both SrS and Ag 2 S. Note that CeOAg 1−x S had also been prepared with difficulty and a rather low yield [21], and a ternary compound BaAg 2 S 2 can be obtained only via an indirect way [23].…”
Section: The Variations Of T-ch Bonds Among Laotch Srftch (T = Cu Amentioning
confidence: 99%
“…This was previously ascribed to nonstoichiometry [24] or to short Ce-S distances [25]. A recent single-crystal study demonstrated that the compound is nonstoichiometric [26]. For this reason a refinement of the structure of CeCuOTe was carried out with the occupancy of the Ce site as an additional variable.…”
Section: Crystallographymentioning
confidence: 99%
“…The Cu/Q materials mostly contain anti-PbO-like [Cu 2 Q 2 ] layers separated by highly ionic atoms or motifs, such as Ba 2+ or the PbO-like [Ln 2 O 2 2+ ] layers. The lanthanum copper oxychalcogenides LaCuOQ have been studied extensively owing to their interesting structure and optical and electrical properties [17][18][19][20][21][22][23][24][25][26]. The important structural feature of this type of compound is the alternation of stacks of [La 2 O 2 ] and [Cu 2 Q 2 ] layers.…”
Section: Introductionmentioning
confidence: 99%